Prostate-specific antigen nadir after high-dose-rate brachytherapy predicts long-term survival outcomes in high-risk prostate cancer - Tsumura, Hideyasu; Satoh, Takefumi; Ishiyama, Hiromichi; Tabata, Ken-ichi; Komori, Shouko; Sekiguchi, Akane; Ikeda, Masaomi; Kurosaka, Shinji; Fujita, Tetsuo; Kitano, Masashi; Hayakawa, Kazushige; Iwamura, Masatsugu (Journal of Contemporary Brachytherapy, 2016)
Purpose : To evaluate the prognostic value of prostate-specific antigen nadir (nPSA) after high-dose-rate (HDR) brachytherapy in clinically non-metastatic high-risk prostate cancer patients. Material and methods : Data from 216 patients with high-risk or locally advanced prostate cancer who underwent HDR brachytherapy and external beam radiation therapy with long-term androgen deprivation therapy (ADT) between 2003 and 2008 were analyzed. The median prostate-specific antigen (PSA) level at diagnosis was 24 ng/ml (range: 3-338 ng/ml). The clinical stage was T1c-2a in 55 cases (26%), T2b-2c in 48 (22%), T3a in 75 (35%), and T3b-4 in 38 (17%). The mean dose to 90% of the planning target volume was 6.3 Gy/fraction of HDR brachytherapy. After 5 fractions, external beam radiation therapy with 10 fractions of 3 Gy was administered. All patients initially underwent neoadjuvant ADT for at least 6 months, and adjuvant ADT was continued for 36 months. The median follow-up was 7 years from the start of radiotherapy. Results : The 7-year PSA relapse-free rate among patients with a post-radiotherapy nPSA level of ≤ 0.02 ng/ml was 94%, compared with 23% for patients with higher nPSA values (HR = 28.57; 95% CI: 12.04-66.66; p < 0.001). Multivariate analysis revealed that the nPSA value after radiotherapy was a significant independent predictor of biochemical failure, whereas pretreatment predictive values for worse biochemical control including higher level of initial PSA, Gleason score ≥ 8, positive biopsy core rate ≥ 67%, and T3b-T4, failed to reach independent predictor status. The 7-year cancer-specific survival rate among patients with a post-radiotherapy nPSA level of ≤ 0.02 ng/ml was 99%, compared with 82% for patients with higher nPSA values (HR = 32.25; 95% CI: 3.401-333.3; p = 0.002). Conclusions : A post-radiotherapy nPSA value of ≤ 0.02 ng/ml was associated with better long-term biochemical tumor control even if patients had pretreatment predictive values for worse control.